Women’s quality of life: university of the third age, goiás, brazil (2010)
Objectives Assessing the quality of life (QOL) of elderly women attending the University of the Third Age (UNATI) at the Federal University of Goiás in Brazil. Methods This was a descriptive, observational study of 38 elderly women aged 60 or older. A socio-demographic information form and the WHOQOL-BREF and WHOQOL-OLD questionnaires were applied for QOL assessment. Results Most women were aged 60-69 (58.8%). The WHOQOL-BREF QOL scores in the physical, psychological, social relationships and environmental domains bore no statistical relevance; however, the general QOL before (67.86±2.91) and after (60.71±8.71) attending UNATI had p=0.049 significance. As for the WHOQOL-OLD, only the sensorial functioning domain (before: 61.84±20.74; after: 71.38±17.66; p=0.014) and the death and dying domain were significant (before: 56.36±25.48; after: 67.27±25.35; p=0.001). Conclusions The elderly women demonstrated typical socio-demographic characteristics and their concerns to stay healthy within possible income, socialisation and health delivery service patterns were considered good. The WHOQOL-BREF revealed that the general domain played a major role compared to other domains. The sensorial functioning and the death and dying domains on the WHOQOL-OLD characterised this particular population’s anxieties, wishes and gender needs.